The Implementation of Think-Pair-Share Technique in Improving Students' Speaking Skill - Maghfira Maghfira (Universitas Cokroaminoto Palopo, 2020)
Abstract This research aims to find out the implementation of Think-Pair-Share technique on speaking skill in improving speaking skill of Physics Students of Tadulako University. The research applied quasy experimental using t-test statistics with non-equivalent control group design. The samples were chosen purposively. The researcher intentionally selected Class B as experimental group and Class D as control group. The instruments of data collection were test to measure students’ speaking. Data were analyzed by using t-test. The result of students speaking skill after taugh by Think-Pair-Share Technique has been improved. It was found that the mean score of students’ speaking skill in experimental group posttest (70.50) is greater than the control group (67). The comparison result through t-test indicates that tcounted value = 3.255 > ttable value = 2.002. Therefore, the implementation of Think-Pair-Share technique has improved students’ speaking skill of Physics Students of Tadulako University. Keywords: Speaking Skill, Cooperative Learning, Think-Pair-Share.